Defining language disorders in children and adolescents with Noonan Syndrome. Issue 4 (14th February 2020) - Lazzaro, Giulia; Caciolo, Cristina; Menghini, Deny; Cumbo, Francesca; Digilio, Maria C.; Capolino, Rossella; Zampino, Giuseppe; Tartaglia, Marco; Vicari, Stefano; Alfieri, Paolo
Abstract: Background: Noonan Syndrome is a developmental disorder characterized by a distinctive phenotype including facial dysmorphism, webbed neck, short stature, heart defects, and variable cognitive deficits as major features. Over the years, neuropsychological and behavioral studies explored alteration of cognitive functioning and related domains, such as learning, memory, and attention. To our knowledge, however, data concerning the language profile in this disorder is scarce. The aim of the present study was to detect specific language functioning combining nonverbal intelligence quotient and language abilities and to pinpoint strengths and weaknesses in the language domains. Methods: The language profile of 37 Italian participants with molecularly confirmed diagnosis of Noonan Syndrome was evaluated using specific tools to assess vocabulary and grammar comprehension and production, as well as phonological development. Results: We observed that 78% of affected individuals exhibited language impairment. Within language domains, the strong area was lexical production and grammar production was the weak area. Almost half the participants manifested a similar trend of specific language impairment. Nonverbal intelligence quotient only correlated with grammar comprehension. Conclusion: Our study expands present knowledge about the language profile in NS, and provides data that could enable more effective patient management and appropriate intervention. Abstract : Little is known about the language profile in Noonan Syndrome. Current results revealed that almost 80% of children from our cohort presented language impairment. Specifically, an area of weakness could be linked to grammar production (52% of children exhibited a below‐average score); conversely, the strength of language profile seemed to be lexical production (81% of children obtained scores on average). The striking data were that almost 50% of individuals presented a "Specific Learning Impairment‐like" trend. Our findings did not mirror the distribution of Specific Learning Impairment in general population ( 7%): thus, it could be read as a syndrome‐specific impairment. The present study also indicated that nvIQ appeared to be positively and moderately associated with grammar comprehension abilities.